ANALISIS PENGARUH PENERIMAAN SISTEM E-LEARNING (PU, PEOU, DAN AIT) TERHADAP MOTIVASI BELAJAR SISWA MENGGUNAKAN MODEL TAM (STUDI KASUS : SISTEM GOOGLE CLASSROOM SMK NEGERI 57 JAKARTA) - Savira Nurfathi (2020)
The presence of the Google Classroom e-Learning system at 57 State Vocational School of Jakarta is a form of utilizing information technology that has begun to be applied for 2 years ago. The use of e-learning systems can be considered as an alternative learning media that has a positive impact and as an effort to increase student motivation. Analysis of system acceptance needs to be done on the practice of new information technology to determine the level of user acceptance in using the Google Classroom e-Learning systems based on the user's perspective, it is proved by using the TAM (Technology Acceptance Model) model. The research was be done by distributing research questionnaires to 144 class X students as research samples. Then the data that has been obtained, is analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method by SmartPLS software. The result of hypothesis testing that have been done proved that the construct of benefits, convenience, and acceptance of the implementation of the Google Classroom e-Learning system influnced in increasing student learning motivation at 57 State Vocational School of Jakarta. This statement is based on the acquisition of the output path coefficient which shows that the construct of Perceived Usefulness has a positive effect of 34% and is significant on the construct of Acceptance of IT with an output value of 0.340. Then, the construct of Perceived Ease of Use has a positive effect of 35.6% and is significant on the construct of Acceptance of IT with an output value of 0.356. Furthermore, the construct of Perceived Ease of Use and Perceived Usefulness together have positive effect of 14.4% and are significant on the construct of Acceptance of IT with an output value of 0.144. The last, the construct of Acceptance of IT has a positive effect of 71.7% and it is significant on the construct of Student Learning Motivation with an output value of 0.717.